Early Aortic Transcatheter Heart Valve Thrombosis. (April 2015) - Leetmaa, Tina; Hansson, Nicolaj C.; Leipsic, Jonathon; Jensen, Kaare; Poulsen, Steen H.; Andersen, Henning R.; Jensen, Jesper M.; Webb, John; Blanke, Philipp; Tang, Mariann; Nørgaard, Bjarne L.
<x xml:space="preserve">Abstract</x> Background— Early stent valve thrombosis after transcatheter aortic valve implantation (TAVI) is a rare complication, which is diagnosed based on the appearance of clinical symptoms of heart failure and echocardiographic findings. After TAVI, transthoracic echocardiography is performed to assess transcatheter heart valve (THV) function. However, preliminary reports indicate the potential additive clinical value of multidetector computed tomography (MDCT) for the diagnosis of THV thrombosis. We sought to determine the value of MDCT for the diagnosis of THV thrombosis and the frequency of this complication after balloon-expandable TAVI. Methods and Results— MDCT was performed in 140 patients within 1 to 3 months after TAVI with the Edwards Sapien XT THV to assess the presence of THV thrombosis and THV stent geometry. Post-TAVI MDCT identified THV thrombosis in 5 patients (4%). Of note, 4 of these patients were asymptomatic and had a normal transthoracic echocardiographic examination without signs of thrombus formation or flow obstruction. In patients with THV thrombosis, a left ventricular ejection fraction of <35% was present in 3 (60%), whereas 2 (40%) did not receive standard post-TAVI dual-antiplatelet therapy. Neither THV underexpansion nor THV noncircularity was detected in patients with THV thrombosis. Conclusions— Post-TAVI MDCT is a valuable tool for the diagnosis of THV thrombosis, and this complication seems to be more common than previously anticipated. Larger studies are required to identify specific risk factors of THV thrombosis.